Transactions of Commodities Results from Buying and Selling (Buyu’) Gharar: Review of Fiqih Muamalah in Batu Basa - Hidayat, Rivaldo Rahman; Yasmin Nabila Kusnawaroh; Hamzah Irfanda; Halim Mustaqim; Hikmatul Fadilah; Fiky Sandez Alfarizi; Aryogo Adi Guna (CV. Kalimasada Group, 2025)
This study examines commodity sales transactions (buyu') containing elements of gharar in Batu Basa from the perspective of muamalah jurisprudence. Gharar, defined as ambiguity or uncertainty in a sale and purchase contract, is prohibited in Islam because it has the potential to harm certain parties and contradicts the principle of justice. This study examines how commodity sales practices in Batu Basa comply with or violate the principle of clarity of the object, price, and transaction contract to avoid gharar. The results indicate that the success of commodity sales transactions depends heavily on transparency and clarity of the contract to avoid elements of gharar, such as uncertainty about the goods sold and uncertain prices. Therefore, the application of muamalah jurisprudence principles that emphasize clarity and mutual agreement in commodity sales in Batu Basa is crucial to maintaining the validity and fairness of transactions and avoiding speculative or fraudulent practices. The implications of this study are encouraging increased understanding and supervision of commodity transactions to ensure they comply with Islamic law